Case Study: Analysis of The Largest Tornado in The Czech Republic from The Perspective of Humanitarian Logistics - Dušan REPÍK; Pavel FOLTIN; Daniel ZLATNÍK (Communications of International Proceedings, 2022)
Humanitarian organisations and Integrated Rescue Services in the Czech Republic are well prepared to face certain types of disasters. These organizations are facing a typical crisis events, in Czech Republic especially floods. However, in the years of 2019 – 2021 there have been a number of shocks - crisis events - that as it was the tornado at the South Moravia region in 2021. The purpose of this paper is to conduct a research of public information on this disaster, consolidate and analyse the information. The available information is analyzed based on a literature search in the Web of Science and Scopus databases and other relevant sources. From these data, the crisis event is described, mapped and the interventions of the Czech government and the Integrated Rescue Services are synthesized. At the same time, the research gap is identified and recommendation for further research are set out.
Keywords: Humanitarian logistics; crisis management; humanitarian supply chain